Public and private capital and public private partnerships series construction for Mozambique, 1960 – 2017 - Huo, Teles (2021)
This article is about the construction of time series on the stock of public and private capital and Public Private Partnerships (PPPs) in Mozambique, from 1960 to 2017, in local currency (meticais), at constant 2009 pries. The construction of these series was based on the IMF methodology, using data on investment and on the depreciation of the capital stock, based on a geometric depreciation model. For investment, data from the National Institute of Statistics (INE) gross fixed capital formation (GFCF), from 1991 to 2017, were considered. For the periods previous to 1991, INE investment data were extended regressively, from 1990 to 1960, considering the proportions of investment in real GDP, by sectors: public, private and PPPs. For this purpose, the proportions of total investment implicit in the IMF data from 1960 to 2013 were used. These proportions were applied to INE GDP data) to obtain the investment data in metical’s at 2009 constant prices, from 1960 to 1990. The result of the capital stock series shows an increasing trend of the total capital stock from 1960 to 2017. From the beginning of the 90's until roughly 2014, the public capital stock exceeded the stock of private capital. The share of the public capital stock in the total capital stock is, in general, greater than the share of the private capital stock. These data shows that despite Mozambique embarked on capitalism, the private sector development remained weak, with a low investment capacity in fixed capital to increase its capital stock.